Web Camouflage Protecting Your Clients from Browser-Sniffing Attacks. - Jakobsson, M.
Browser cache and history are intended to be private, yet it's not difficult for malicious Web sites to "sniff" cache entries on visitors' computers and then use that information to more accurately deceive them. The authors' approach neutralizes the threat of URLs being discovered on client computers.
Keywords: URL threat; Web camouflage; Web privacy attacks; Browser cache; Browser history; Browser-sniffing attacks; Client computers; Malicious Web sites